Assessing water dependencies and risks in Dutch industries: Distribution, consumption and future challenges - C.J. Teo; J. Poinapen; J.A.M.H. Hofman; T. Wintgens (Water Resources and Industry)
This research examined the water dependencies and associated risks in Dutch industries by focusing on three main aspects: the geographical distribution of industrial clusters relative to water sources, water consumption and its economic value across different sectors, and future water stress scenarios with their regional implications. The study uncovered a complex relationship between industrial facility location and water use. It revealed a strong correlation between facilities and nearby water sources, with a tendency for industries to cluster around water sources, peaking at a proximity of about 0–5 km for both surface water and groundwater sources. However, it also pointed out that this relationship is influenced by several other factors including water quality, extraction rights, historical development, and competition for water resources. Additionally, the analysis underlined the importance of considering both water consumption and proximity to water sources to accurately assess dependency. It advocated a more sophisticated approach that moves beyond mere water usage per unit of output to encompass the production complexities that significantly affect water dependency in particular industries. The future projection showed baseline water stress impacts the security of water supply of industries at different magnitude. Particularly, North Brabant and Limburg stood out as particularly vulnerable. These regions hold a significant portion of the studied industrial facilities (21.7 %) and dominate the nation's mineral industry (75 %). The study acknowledged the drawbacks of depending solely on average sectoral data and stresses the urgency for proactive water management strategies. These insights laid a solid groundwork for further research and the implementation of targeted water conservation and sustainable production measures within the Dutch manufacturing sector and beyond as water management issues have global relevance. This study suggested areas for further exploration such as exploring different circular water strategies, industrial symbiosis, leveraging digital technology for optimising water management, and utilising alternative water sources.